A Textual History of Mozilla: Using Topic Modeling to Trace Sociocultural Influences on Software Development. - Black, Michael L. (DHQ: Digital Humanities Quarterly, 2015)
This essay applies a digital humanities methodology to the study of digital media by framing software history as a problem of big data and textual criticism. While many scholars have already identified source code as an important site for the cultural study of software, this essay proposes that close reading is not suited to the scale and scope of modern application software. Applying text analysis tools to large bodies of source code can help address these problems as well as provide a basis for narrativizing its development and contextualization amidst a complex network of economic, political, and other sociocultural processes. Using source code produced over 15 years of development by the Mozilla foundation, this essay argues that software interfaces act as an extension of public relations narratives, often representing a developer's idealized version of their software which may not necessarily correspond with the state of the application's source code. Topic modeling Mozilla's source code allows us to explore a more nuanced narrative of development that shows how Mozilla has negotiated between the political ideals of open source software and the corporate ideology of its parent companies.